Manufacture and testing of ARGUS: A pole climbing surveillance robot - de Ronde Willis; Bosscha Peter; Marais Stephen; Pretorius Arnold (MATEC Web of Conferences)
South Africa needs rapidly deployable surveillance in situations such as public marches and periods of unrest. As these events can often last several hours, short-term solutions, such as multi-rotor drones, are generally not feasible. The proposed solution, the Automated Robotic Guardian for Urban Surveillance (ARGUS) platform, is a rapidly deployable pole-climbing robot for surveillance and situational awareness. This paper outlines the system's manufacture, testing, and analysis. The platform was tested under various laboratory and real-world conditions against predefined user specifications. Test results demonstrate that the system can ascend and descend multiple existing pole infrastructures and maintain a hold position without the motors consuming power while on the pole.